2021
DOI: 10.1177/03057356211024344
|View full text |Cite
|
Sign up to set email alerts
|

A PRISMA review of expectancy-value theory in music contexts

Abstract: In this article, we systematically reviewed the research literature dealing with expectancy-value motivation theory within music contexts. Employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, a total of 1,120 records were retrieved and examined, with 110 eventually included in the analyses. Frequencies/percentages were generated for research output in 5-year time periods, type of publication, sampling locations, and methodologies. Summaries of all 110 records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Theory of expectation and value: Based on the theoretical model proposed by Atkinson (1983), Eccles (2005) proposed a model in which the individual feels motivated for a given task according to importance, interest, utility, and cost as components of value (Sin et al, 2022).…”
Section: Motivation Theories and The Ecological Theory Of Human Devel...mentioning
confidence: 99%
“…Theory of expectation and value: Based on the theoretical model proposed by Atkinson (1983), Eccles (2005) proposed a model in which the individual feels motivated for a given task according to importance, interest, utility, and cost as components of value (Sin et al, 2022).…”
Section: Motivation Theories and The Ecological Theory Of Human Devel...mentioning
confidence: 99%
“…Previous research has shown that perceived barriers, such as cost, can negatively affect students' intentions to use technology in education (Chan & Hu, 2023;Flake et al, 2015;Regmi & Jones, 2020;Stüber, 2018). The expectancy-value framework has been widely used in educational research to examine students' motivation, learning, and achievement (Cheng et al, 2020;Sin et al, 2022).…”
Section: Expectancy-value Theory and Other Frameworkmentioning
confidence: 99%
“…Costs refer to the efforts or sacrifices related to activity participation. Research findings suggest that cost negotiation plays a vital role in decision-making, but researchers and music educators may too often overlook the role of costs in activity involvement (Hawkinson, 2015; Pendergast & Robinson, 2020; Sin et al, 2021). EVT theorists cite four types of costs: effort-related, effort-unrelated, loss of valued alternatives, and psychological costs.…”
Section: Expectancy Value Theory: Self-efficacy Value Costs and Barriersmentioning
confidence: 99%